Intervention Fidelity in Mindfulness-Based Research and Practice: Developing Criteria to Acknowledge New Training Programs. (23rd December 2022) - van Boxtel, Martin P. J.; Sansom, Sophie A.; Kersemaekers, Wendy
The field of mindfulness-based research and practice is expanding fast. This development calls for a careful evaluation of the merits and scientific underpinnings of newly developed mindfulness-based programs (MBP's). In this viewpoint, we describe a process initiated by two professional mindfulness teacher training organisations (the Dutch Vereniging Mindfulness-based Trainers Nederland, VMBN, and the British Association of Mindfulness-based Approaches, BAMBA) to develop a framework for evaluating the integrity of newly developed MBP's. The framework aims to articulate criteria describing the elements and processes required to ensure that a new MBP meets good practice, adheres to evidenced-based practice, and is attending to the challenge of implementation and scalability. The development and implementation of the criteria are still a 'work in progress'. We hope that this initiative offers a foundation for supporting the MBP field to balance innovation and grassroot community development with aligning to the principles of evidence-based practice.